Hands-on gravity estimation with STATA - Cipollina, Maria; Salvatici, Luca (International Food Policy Research Institute, 2012)
In this document we give several examples of hands-on estimation to familiarize yourself with the gravity equation methodological choices highlighted in the literature review. This guide provides an illustrative dataset with alternative Stata codes presenting the different possible estimation strategies.